Pengaruh Jumlah Anggota, Modal Sendiri dan Volume Usaha Terhadap Sisa Hasil Usaha Koperasi - Sayidil Umam, Mochamad Febri; Riyadi, Wulan; Rusdiana, Alan (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2024)
This study aims to find out how the effect of the number of members, own capital and business volume on the remaining results of operations in cooperative groups based on districts/cities in West Java Province either partially or simultaneously. The research method used is descriptive analysis and verification analysis. The population in this study is cooperative groups based on districts/cities in West Java Province which are listed on the West Java Provincial Government Website for the 2017-2021 period. The sample in this study used a saturated sampling technique so that sample data were obtained from 27 districts and cities consisting of 18 districts and 9 cities with a total sample data of 135. The results of this study partially show that the number of members has no significant effect on the remaining business results. Own capital and business volume have a significant effect on the remaining operating results. Meanwhile, it simultaneously shows that the number of members, own capital and business volume have a significant effect on the remaining business results.